Complementing Scenario Planning to the Strategic Value of Corporate War Gaming for Foresight and Decision-Making - Azarcon, Rizza Mae C.; Grefalde, James Q. (International Review of Management and Marketing, 2026)
Corporate war gaming is becoming more widely regarded as a complementary approach to classic scenario planning in assisting organizations during uncertain and complex times. Scenario planning has been used for decades to prepare for uncertain exogenous circumstances and provide long-haul foresight, but its descriptive and narrative approach does not appropriately capture competitive dynamics and hidden risks. Corporate war gaming offers experiential, role-play simulations that progressively stress-test strategies against adversarial environments and responses from stakeholders. This paper examines how corporate war gaming complements scenario planning and ultimately creates value in an organization’s decision-making process. Qualitative research design was employed in this study to answer this question by leveraging semi-structured interviews with fourteen individuals who acted as key informants across various sectors, and data were analyzed using Braun and Clarke’s thematic analysis process. The findings produced six themes—active simulation, strategic agility and readiness, revelation of blind spots, integration of competitors and stakeholders’ perspective, cross-functional collaboration, and multi-level application, which together demonstrate how a war game aspires to transmute foresight in planning to rehearsed action. Given these findings, the study finds that corporate war gaming can enhance organizational agility, resilience, and strategic readiness in dynamic environments when coupled with scenario planning.